2012
DOI: 10.4028/www.scientific.net/amr.562-564.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ZnO Buffer Layer Thickness on AZO Film Properties

Abstract: To evaluate the influence of the ZnO buffer layer thickness on structural, electrical and optical properties of ZnO: Al (AZO)/ZnO bi-layer films, a series of AZO/ZnO films were deposited on the quartz substrates by electron beam evaporation. X-ray diffraction measurement shows that the crystal quality of the films is improved with the increase of the film thickness. The electrical properties results show that the resistivity decreases initial and then increases. However, optical transmittance of all the films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…From the graph shown, sample S5 have the lowest reflectance percentage of approaching 60 percent and followed by S4 (80 percent) and S3 (85percent). However, S2 and S1 are in the range of 90 percent that represent high crystal quality of the film [9]. It is also observed that the percentage of reflectance spectra for a small photon energy of these five samples are increasing as the PANi concentration in the sample decrease.…”
Section: Resultsmentioning
confidence: 80%
“…From the graph shown, sample S5 have the lowest reflectance percentage of approaching 60 percent and followed by S4 (80 percent) and S3 (85percent). However, S2 and S1 are in the range of 90 percent that represent high crystal quality of the film [9]. It is also observed that the percentage of reflectance spectra for a small photon energy of these five samples are increasing as the PANi concentration in the sample decrease.…”
Section: Resultsmentioning
confidence: 80%
“…Various solutions are currently studied. The first approach, based on classical well mastered deposition methods, [2] is oriented towards the doping of n-type semiconductors to obtain optimized layers, for example Al-doped ZnO (AZO) [3] or F-doped SnO2 (FTO) oxides. A second approach concerns the application of new techniques or modifications of existing ones to be applied for the nano-structuring of these TCO layers.…”
Section: Introductionmentioning
confidence: 99%